Relação de trabalho por aplicativos: uma verificação da presença dos requisitos da relação de emprego - Valentim, Leandro Kuster (2019)
Introduction: Nowadays, the advancement of technology and the internet have been modifying labor relations, highlighting, among them, regulated employment, with employment contracts and social protection, which has been questioned in times of intense use of micro-informatics and new forms of employment. Communication. Technologies of a diverse nature have been absorbed by companies, the public sector, and recently startups, notably the applications (APPs) that flood people's lives, with a variety of functions: bank account use and management, doctor appointments and psychological issues, online shopping, food ordering and, more recently, those who claim to be service intermediaries. As a contextualization, it is considered that the latter seem to have created a breaking point in the norms that regulate the way institutions manage the people they hire. In the case of PPAs, this management is evidenced by the lack of standardization, flexibility and precariousness of labor relations, used in the name of valuing freedom, low cost and ease, to the detriment of labor regulation and guarantees, problem to research. Therefore, the verification of the functioning of these applications in the context of laws aimed at worker protection is crucial. Thus, the present research aimed to verify if the necessary elements to characterize the employment bond are present in the labor relations intermediated by Parafuzo application, in the hiring of day labor services. The theoretical foundation was based on the legal system that supports the elements that characterize the employment bond, as well as the material related to the theme. To achieve the proposed objective, among the methods and procedures, qualitative research was used, exploring, as research sources, labor legislation, scientific articles and the Parafuzo application website, on which the content analysis technique was applied. The research corpus consisted of materials collected on Parafuzo's website, including videos made available there. This material went through sequential readings, in which we searched for elements that could characterize the categories defined ex-ante, based on the legal order, namely: Individual, Personality, Onerosity, Non-eventuality and Subordination. The treatment of the data found and collected occurred through their confrontation with what is recommended by the legislation. The results revealed the presence of all elements that characterize the employment relationship in the intermediation promoted by the studied application. The research was developed in the Technology, Innovation and Public Sector Operations line, with emphasis on the regulation of labor relations. As a technical product, a technical report has been developed for the Labor Tax Audit of the Ministry of Economy, the content of which may be appropriated by the labor inspectorate when planning and executing tax actions for this new modality of service provision.